413 Effects of various concentrations of soybean hull supplementation on performance of weaned beef cattle fed ryegrass baleage. (7th December 2018) - Tipton, P; Rivera, J; Johnson, J; Lutz, A
Abstract: A study was conducted to evaluate the effects of feeding graded concentrations of soybean hull pellets (SHP) on performance of weaned beef calves that were fed baleage. Sixty beef calves (216.2 ± 7.5 kg) were blocked by sex, stratified by BW and placed into 12 pens (five calves per pen), pens were randomly assigned treatments. Treatments were: 0.0%, 0.5% (0.5), or 1% (1.0) BW of soybean hull pellets fed daily while calves had ad libitum access to ryegrass baleage. Body weight and blood were collected on d 0, 28 and 47, for subsequent serum chemistry analyses. Baleage was weighed at offering and refusals were collected and weighed to calculate disappearance. Body weight tended to increase when either 0.5% or 1.0% SHP were fed (P < 0.1) at day 28; however increasing SHP increased BW at d 47 (P = 0.002). Increasing SHP resulted in greater ADG from d 0 to 28 (P < 0.003) and from d 0 to 47 (P < 0.003). Dry matter intake of baleage tended to be affected by SHP (P =0.06), with SHP decreasing baleage DMI; however no differences were noted between 0.5 and 1.0 SHP. From d 29 to 47 DMI of baleage decreased (P = 0.05) with SHP supplementation, but did not differ between supplement levels (P = 0.97). Similarly, total baleage DMI decreased with SHP (P = 0.01) but did not differ between supplement levels (P = 0.86). Results suggest that increasing SHP supplementation can improve performance without affecting baleage intake.